2013
DOI: 10.11604/pamj.2013.16.16.2644
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a five year experience of permanent pacemaker implantation at a Nigerian Teaching Hospital: need for a national database

Abstract: IntroductionPermanent pacemaker implantation is available in Nigeria. There is however no national registry or framework for pacemaker data collection. A pacemaker database has been developed in our institution and the results are analyzed in this study.MethodsThe study period was between January 2008 and December 2012. Patient data was extracted from a prospectively maintained database which was designed to include the fields of the European pacemaker patient identification code.ResultsOf the 51 pacemaker imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 18 publications
1
16
1
3
Order By: Relevance
“…There are few reported series on pacemaker implantation in Nigeria. This is a slowly evolving practice, mainly due to the cost of pacemaker implantation (14) and limited expertise (15). Both single and dual chamber implantation is performed.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reported series on pacemaker implantation in Nigeria. This is a slowly evolving practice, mainly due to the cost of pacemaker implantation (14) and limited expertise (15). Both single and dual chamber implantation is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies on bradyarrhythmias and CIEDs in SSA were identified through the systematic search [9,11,12,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] (Figure 1). Table 4 depicts 13 of these studies with some uniform data that could be organized into one table.…”
Section: Indications Of Device Implantation Type Of Devicementioning
confidence: 99%
“…The commonest indication for permanent pacing in SSA is atrioventricular block (AVB) accounting for 45-100% of all cases across studies, compared to sick sinus syndrome at 0-35%, and others (atrioventricular node ablation, cardiac re-synchronization therapy, etc) 0-20%. Single chamber ventricular (VVI) pacemakers are the most frequently implanted (17-87%), compared to dual chamber (12-82%), and others like atrial-sensed ventricular-paced (VDD) (0-15%) [107][108][109][110][111][112][113][114][115][116][117]120]. Cost constraints have been identified as the reason for high implant percentage of VVI compared to DDD [114].…”
Section: Indications Of Device Implantation Type Of Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Bradyarrythmias are a cause of sudden death everywhere in the world, although the precise incidence is unknown. Pacemaker implantation is an accepted intervention which has been shown to improve the quality of life and reduce mortality in patients with bradyarrythmias (Falase et al, 2013). Kashmir valley is inhabited by a relatively homogenous inbreeding population with dietary practices and living conditions that do not differ significantly across the valley.…”
Section: Discussionmentioning
confidence: 99%